Jozi play (museum) : preserving the place of play - Pretorius, Nicolé Natalie (My University, 2017)
This thesis studies the place and nature of the concept of play in society through the exploration of objects and spaces that stimulate, encourage or deter the notion of play. Nominated spaces that will ideally contribute to the study of play are reviewed, focusing in particular on areas within the local context of Johannesburg where a notion of play takes or could inherently take place. But in order to draw an understanding and a cognitive inspiration, toys are reviewed as objects of play. Toys are studied with the intention of identifying the role it encompasses and the integrity of the notion of play, with a focus on local toy design and manufacture in relation to the international market.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Architecture (Professional), Johannesburg 2017
Keywords: Public spaces--South Africa--Johannesburg--Design; Public architecture--South Africa--Johannesburg--Designs and plans; City planning--Environmental aspects--South Africa--Johannesburg; Architecture--Human factors--South Africa--Johannesburg